2017
DOI: 10.12968/jpar.2017.9.8.330
|View full text |Cite
|
Sign up to set email alerts
|

Durham and Cleveland police firearms unit tactical team medics: lessons from the first six years

Abstract: Background. Since 2007 Durham and Cleveland Firearms Police have trained a small number of firearms police officers to an enhanced level of first aid qualification. This article reviews the history of this programme, the patient report forms submitted during the period 2013-2016 and analyses the types of incidents attended. Methods: 66 PRFS were interrogated and analysed from a four-year period between Jan 2013 and Dec 2016. There was a marked increase in PRFs submitted during that time. Over half the casualti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…This continued collaboration has cemented strong links with the larger military family and sees the regular involvement of specialist clinicians from all three services supporting the programme as an evolving teaching faculty, in addition to support from the pathology service (see Figure 3). The use of tourniquets, haemostatic wound dressings, chest seals and oxygen therapy is now commonplace and has contributed greatly to improving patient outcomes 5…”
Section: Medical First Respondersmentioning
confidence: 99%
See 1 more Smart Citation
“…This continued collaboration has cemented strong links with the larger military family and sees the regular involvement of specialist clinicians from all three services supporting the programme as an evolving teaching faculty, in addition to support from the pathology service (see Figure 3). The use of tourniquets, haemostatic wound dressings, chest seals and oxygen therapy is now commonplace and has contributed greatly to improving patient outcomes 5…”
Section: Medical First Respondersmentioning
confidence: 99%
“…One such study, ‘ Durham and Cleveland police firearms unit tactical team medics: lessons from the first 6 years ’,analysed PRF data collected over a 4-year period, as part of the forces’ TTM programme in support of their Clinical Governance framework 5. The evidence suggests that like many other similar programmes, police officer more often use their trauma first aid skills at incidents such as road traffic collisions, assaults or self-harm incidents rather than for the treatment of firearms-related injuries.…”
Section: Medical First Respondersmentioning
confidence: 99%
“…First Official Journal of the Australian Tactical Medical Association(Hartley et al, 2017 andCarr et al, 2017). Both papers acknowledge that the numbers of PRFs examined are likely to be underrepresentative of the true number of incidents encountered by officers.…”
mentioning
confidence: 99%
“…In their examination of 66 patient report forms (PRFs) submitted by Module 5 trained firearms officers in two forces over a period of four years,Carr et al (2017) found that on-scene times ranged from five minutes to over an hour. About half of the PRFs saw officers managing a casualty for up to twenty minutes, with the other half being between twenty minutes and an hour, but the reasons for this were not explored.…”
mentioning
confidence: 99%